Circulatory proteins relate cardiovascular disease to cognitive performance: A mendelian randomisation study - Huang, Jian; Gill, Dipender; Zuber, Verena; Matthews, Paul M.; Elliott, Paul; Tzoulaki, Ioanna; Dehghan, Abbas (Frontiers in Genetics, 2023)
Background and Objectives Mechanistic research suggests synergistic effects of cardiovascular disease (CVD) and dementia pathologies on cognitive decline. Interventions targeting proteins relevant to shared mechanisms underlying CVD and dementia could also be used for the prevention of cognitive impairment. Methods We applied Mendelian randomisation (MR) and colocalization analysis to investigate the causal relationships of 90 CVD-related proteins measured by the Olink CVD I panel with cognitive traits. Genetic instruments for circulatory protein concentrations were obtained using a genome-wide association study (GWAS) meta-analysis from the SCALLOP consortium (N=17,747) based on three sets of criteria: 1) protein quantitative trait loci (pQTL); 2) cis-pQTL (pQTL within ±500kb from the coding gene); and 3) brain-specific cis-expression QTL (cis-eQTL) which accounts for coding gene expression based on GTEx8. Genetic associations of cognitive performance were obtained from GWAS for either: 1) general cognitive function constructed using Principal Component Analysis (N=300,486); or, 2) g Factor constructed using genomic structural equation modelling (N=11,263-331,679). Findings for candidate causal proteins were replicated using a separate protein GWAS in Icelanders (N=35,559). Results A higher concentration of genetically predicted circulatory myeloperoxidase (MPO) was nominally associated with better cognitive performance (P<0.05) using different selection criteria for genetic instruments. Particularly, brain-specific cis-eQTL predicted MPO, which accounts for protein coding gene expression in brain tissues, was associated with general cognitive function (βWald=0.22, PWald=2.4×10-4). The posterior probability for colocalization (PP.H4) of MPO pQTL with the g Factor was 0.577. Findings for MPO were replicated using the Icelandic GWAS. Although we did not find evidence for colocalization, we found that higher genetically predicted concentrations of cathepsin D and CD40 were associated with better cognitive performance and higher genetically predicted concentration of CSF-1 were associated with poorer cognitive performance. Discussion We conclude that these proteins are involved in shared pathways between CVD and those for cognitive reserve or affecting cognitive decline, suggesting therapeutic targets able to reduce genetic risks conferred by cardiovascular disease.